Global profiling of Huntingtin-associated protein E (HYPE)-mediated AMPylation through a chemical proteomic approach - Broncel,M; Serwa,RA; Bunney,TD; Katan,M; Tate,EW (Molecular & Cellular Proteomics, 2015)
AMPylation of mammalian small GTPases by bacterial virulence factors can be a key step in bacterial infection of host cells, and constitutes a potential drug target. This posttranslational modification also exists in eukaryotes, and AMP transferase activity was recently assigned to HYPE Filamentation induced by cyclic AMP domain containing protein (FICD) protein, which is conserved from Caenorhabditis elegans to humans. In contrast to bacterial AMP transferases, only a small number of HYPE substrates have been identified by immunoprecipitation and mass spectrometry approaches, and the full range of targets is yet to be determined in mammalian cells. We describe here the first example of global chemoproteomic screening and substrate validation for HYPE-mediated AMPylation in mammalian cell lysate. Through quantitative mass-spectrometry-based proteomics coupled with novel chemoproteomic tools providing MS/MS evidence of AMP modification, we identified a total of 25 AMPylated proteins, including the previously validated substrate endoplasmic reticulum (ER) chaperone BiP (HSPA5), and also novel substrates involved in pathways of gene expression, ATP biosynthesis, and maintenance of the cytoskeleton. This dataset represents the largest library of AMPylated human proteins reported to date and a foundation for substrate-specific investigations that can ultimately decipher the complex biological networks involved in eukaryotic AMPylation.